INTERPRETATIONS OF THE PHILOSOPHICAL LEGACY OF VOLODYMYR SHYNKARUK IN THE WORKS OF VITALII TABACHKOVSKYI - АНАТОЛІЙ ВОВК (Cхід, 2021)
The emergence of various interpretations of the legacy of Volodymyr Shynkaruk is caused not only by the texts of the classic of modern Ukrainian philosopher and facts from the histo-ry of philosophical thought development in Ukraine in the second half of the 20th century, but also by the struggle of various narratives that already exist or are offered by philosophers to tell about the fate of philosophy in Kyiv in Soviet and post-Soviet times. The discussion about the identity of Volodymyr Shynkaruk's philosophy arose in the late 1990s and early 2000s in connection with the publication by V.H. Tabachkovskyi of a number of articles and chapters in books devoted to the interpretation of the figure of V. Shynkaruk as the founder of the Kyiv anthropological school. Vitalii Tabachkovskyi tried to substantiate and reveal a cer-tain narrative about the Kyiv Philosophical School as the central mainstream in the philo-sophical sixties, as well as a narrative about the phenomenon of philosophical sixties as a kind of manifestation of liberalism and dissidence regarding the official ideology and philos-ophy. Many distortions of the true meaning of the texts of Kyiv philosophers occurred through reading them not in their own context and meanings, but through guessing what similar philosophical concepts are in world thought. Vitalii Tabachkovskyi's method of anal-ogies and his attempts to look at Volodymyr Shynkaruk's work through the prism of analo-gies with modern trends develop in his book and many articles. Despite the desire to posi-tively accept Vitalii Tabachkovskyi's reasoning about Volodymyr Shynkaruk's philosophical views, we cannot do this, as his reflections at certain points obviously contradict Volodymyr Shynkaruk's texts.